SYNTACTIC VARIATION OF MAKASSARESE, A MEMBER OF THE SOUTH SULAWESI GROUP OF LANGUAGE IN AUSTRONESIAN GREAT FAMILY, CLASSROOM LANGUAGE ASSESSMENT - Weda, Sukardi (PEOPLE: International Journal of Social Sciences, 2017)
Makassarese belongs to the member of the South Sulawesi group of the great family of Austronesian languages of Indonesia which is spoken by 2,130,000 (2000 census). Their homeland is South Sulawesi but many of them live in other provinces in Indonesia. This research aims to investigate sentence structure of Makassarese as a member of the Malayo-Polynesian branch of the Austronesian language family. The study employed qualitative approach in which the researcher asked the subjects to write down the equivalent of Indonesian language in Makassarese. The Indonesian sentences consisting of 15 sentences. The subjects were the students of Graduate Program who attended Morphosyntax subject. The research finding reveals that Makassarese has two basic sentence patterns in terms of its syntactic variation, they are SVO and VSO. In Makassarese, pronoun ‘I’ has two forms, independent pronoun ‘Inakke’ (I) and ergative pronoun ‘-ka’ (I). Makassarese speakers employ some sentence patterns and pronouns with various purposes and functions.